The Roles Of Personal, Relational, And Environmental Factors On Women Empowerment In Public Organisations In Saudi Arabia - Afridi, Zahra (2023)
The current study is trying to evaluate women's empowerment through different factors such as training, inter-gender communication, and organisational policies of top management of public organisations of Saudi Arabia. The current proposed model is underpinned by empowerment and gendered organisational theories.